2021
DOI: 10.1007/s11469-021-00536-9
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19-Related Lockdown in Qatar: Associations Among Demographics, Social Distancing, Mood Changes, and Quality of Life

Abstract: The worldwide spread of the coronavirus disease (COVID-19), the absence of medical treatment and vaccination, the delayed onset of symptoms, and the rapid human-to-human transmission have led the vast majority of countries to impose strict social distancing procedures. Whereas it appears that social distancing is an effective strategy for mitigating spread, it may also result in a variety of unintended negative consequences to individuals’ psychological well-being and mental health. During the peak of the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
1
4
0
1
Order By: Relevance
“…In this context, the current study explored the relationship between fear of the coronavirus, coping strategies, and depressive symptoms among nursing students. Our results were interpreted in light of previous and similar literature that estimates the prevalence of mental health issues among healthcare workers [ 28 – 33 ].…”
Section: Discussionsupporting
confidence: 76%
“…In this context, the current study explored the relationship between fear of the coronavirus, coping strategies, and depressive symptoms among nursing students. Our results were interpreted in light of previous and similar literature that estimates the prevalence of mental health issues among healthcare workers [ 28 – 33 ].…”
Section: Discussionsupporting
confidence: 76%
“…As well, fourth year students were the most committed to social distancing instructions and were most physiological affected by social distancing in term of increased using of the internet and social aspects. Since these students were oldest and older ages were generally more content with the social distancing situation than the younger Megreya et al 2021). Also, may be due to that these students are in their last year at the university and of course their concerns about their future are high.…”
Section: Figure1mentioning
confidence: 99%
“…Another research study that was conducted by Megreya et al (2021), that evaluates the impacts of Covid-19 during the lockdown in Qatar that aimed to investigate the linkages between the various demographic variables, and its reflection on the social distancing situation and intended to explore the occurrences of the moon changes among the inhabitants, and the general quality of life. The results of the study were outstanding, as they revealed that respondents of older ages, also the married respondents, and the employed ones were generally more content with the social distancing situation than the younger, unmarried, and unemployed ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Data reported in Figure 10 can be collected from a variety of devices, apps, and search engines, to name a few. IoT data can be collected from wearable sensors [65], contents, and other related data can be gathered from e-commerce websites [66], mobile data can be gathered from mobile carriers/service-providers, social media data can be collected from SN service providers [67], historical data can be gathered from the hospitals websites/repositories [68], medical images and sounds data can be collected with wearable devices or automated machines, and demographics data can be obtained from trusted clinics/hospitals [69]. The logistic regression based models can assist in identifying hotspots in any territory based on the certain environment parameters and underlying conditions [70].…”
Section: Perspective 3: Epidemic Handling With Heterogeneous Sources Data and Ai Rolementioning
confidence: 99%